2019
DOI: 10.28940/terra.v37i1.304
|View full text |Cite
|
Sign up to set email alerts
|

La fertilidad del suelo afecta el crecimiento, nutrición y rendimiento de algodón cultivado en dos sistemas de riego y diferentes dosis de nitrógeno.

Abstract: Intrinsic soil fertility and the method of irrigation can affect the efficiency of nitrogen (N) fertilization, modify the yield goal, growth, and nutritional status of crops. A study was carried out with the objective of determining yield, growth, water use efficiency (WUE), agronomic efficiency of N (AEN), NO3- concentration in petiole cell extract (PCE) and chlorophyll index (SPAD) in a cotton crop by effect of N rates and two irrigation methods. The study consisted of two experiments established in soils of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…El algodón se encuentra entre los cultivos más explotados, cuyos rendimientos dependen en gran medida del riego eficiente del cultivo, lo cual además de aumentar la productividad, también optimiza la calidad de los productos cosechados, esta práctica agronómica junto con el uso fertilizante resulta ser uno de los factores con mayor efecto sobre el rendimiento del cultivo de algodón (Santillano-Cazares et al, 2019).…”
Section: Requerimientos Nutricionales Del Cultivo De Algodónunclassified
See 1 more Smart Citation
“…El algodón se encuentra entre los cultivos más explotados, cuyos rendimientos dependen en gran medida del riego eficiente del cultivo, lo cual además de aumentar la productividad, también optimiza la calidad de los productos cosechados, esta práctica agronómica junto con el uso fertilizante resulta ser uno de los factores con mayor efecto sobre el rendimiento del cultivo de algodón (Santillano-Cazares et al, 2019).…”
Section: Requerimientos Nutricionales Del Cultivo De Algodónunclassified
“…La integración de fertilizantes orgánicos en los sistemas de producción de algodón se muestra como una alternativa a los sistemas actuales de producción de algodón a pequeña escala, dado que integra elementos del subsistema de producción animal en el desarrollo de la granja, combinando estiércol de cerdo, estiércol de pollo y biofertilizantes líquidos como alternativas sostenibles que garantizan aportes altos de nitrógeno y fósforo al suelo (Santillano-Cazares et al, 2019).…”
Section: Efectos De La Fertilización Orgánica Sobre El Crecimiento Y ...unclassified
“…Remote sensing data has been employed to accurately assess forest biochemical compositions on broad spatial scales, and various researches developed models to relate reflected spectra to the observed vegetation parameters (Chlus & Townsend 2022;Shen et al 2020). The growth status of plant are linked to soil fertility, and sufficient nutrients support vegetation growth and development (Santillano Cázares et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [ 9 ] have shown that the NO 3 − –N content in the last four leaf petioles of cotton during the bud stage is significantly correlated with yield, which can sensitively indicate the N nutrition status of cotton and serve as a recommended diagnostic period for cotton topdressing.The accuracy of cotton yield prediction is directly related to the fertilization level during important growth periods [ 19 ]. Therefore, reliable prediction methods [ 18 ] can help excessive fertilizer application, reduce environmental pollution and unnecessary costs [ 20 ]. With the rapid rise of artificial intelligence, neural network technology [ 21 ] provides new methods and approaches for agricultural applications.…”
Section: Introductionmentioning
confidence: 99%